Sleep satisfaction and problematic smartphone use among adolescents in the Republic of Korea: The mediating roles of anxiety and loneliness - Jiyeon Kim; Myongsun Cho (PLoS ONE, 2026)
Problematic smartphone use (PSU) has become a growing public health concern among adolescents, with global prevalence estimates ranging from 10% to 30%. Sleep dissatisfaction has been identified as a potential risk factor for PSU. However, the psychological mechanisms underlying this association remain unclear. This study examined the relationship between sleep satisfaction and PSU among Korean adolescents, and investigated the mediating roles of anxiety and loneliness. Data were collected from 48,829 adolescents who were categorized into three groups: general users (72.1%), potential-risk users (24.8%), and high-risk users (3.1%). Group differences were examined using chi-square tests and one-way analysis of variance (ANOVA). Multivariate logistic regression analyses were conducted to identify the factors associated with PSU risk. Mediation analyses were conducted using a counterfactual framework to estimate the total, natural direct, and natural indirect effects of sleep satisfaction on PSU risk through anxiety and loneliness. Increased PSU risk was significantly associated with being female, high smartphone usage time (≥4 hours/day), and reporting poor perceived health. High-risk users reported markedly longer daily smartphone use (7.01 ± 0.12 hours) and significantly higher anxiety and loneliness scores compared to other groups ( p < .001). Poor sleep satisfaction and insufficient physical activity were also significantly associated with higher PSU risk. Mediation analyses indicated significant natural indirect effects through anxiety and loneliness, with proportions mediated of 30.0% and 15.2%, respectively. Sleep dissatisfaction is significantly associated with problematic smartphone use among adolescents, and this relationship is partly explained by heightened anxiety and loneliness. Interventions aimed at improving sleep satisfaction and addressing emotional vulnerability may be effective strategies for reducing the PSU risk in this population.